Peran Pendidikan Islam dalam Membangun dan Menguatkan Worldview Islam padaMasyarakat Muslim di Tengah Arus Globalisasi - Wahyudi, Tian (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2017)
This article describes about two things. First, the urgency of the Islamic world view for the Muslim community. This is important because Islam has a view of life which is different from the others. In addition, it is also a response to globalization identified Westernization. The study of scientists show that Western hegemony of Muslim society covers various fields including sciences and thoughts. This Western hegemony ultimately influences the Muslim world view. Even though the world view is a principle for understanding the reality that affect the attitude and behavior of individuals. In fact, it can be a driving force for social change. Second, the role of Islamic Education in inculcating the Islamic world view for the Muslim community. This begins with the notion that there is a close correlation between education and world view. Islamic education is the main instrument for creating the quality of Muslim, and it originates from the inculcating and reinforcement of the Islamic world view. To strengthen the role, Islamic education should make the Islamic world view as a reference in building its educational system.ØØ§ÙÙØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø¯Ø±Ø§Ø³Ø© : 1) Ø£ÙÙÙØ© ÙÙÙ Ø§ÙÙØ¸Ø±Ø© Ø§ÙØ¹Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙÙØ¬ØªÙØ¹ Ø§ÙÙØ³ÙÙ. ÙÙØ°Ø§ ÙÙÙ ÙØ£Ù Ø§ÙØ¥Ø³ÙØ§Ù ÙÙ ÙØ¸Ø±ØªÙ Ø§ÙØ®Ø§ØµØ© Ø§ÙÙØ®ØªÙÙØ© Ø¹Ù ØºÙØ±Ù ÙÙ Ø§ÙØ£Ø¯ÙØ§Ù. ÙØ¨Ø¬Ø§ÙØ¨ Ø°ÙÙØ Ø£ØµØ¨ØØª ÙØ°Ù Ø§ÙÙÙØ§ÙØ© Ø§Ø³ØªØ¬Ø§Ø¨Ø© ØªØ¬Ø§Ù Ø§ÙØ¹ÙÙÙØ© Ø§ÙÙØ±ÙØ¨ ÙØ¹ÙØ§ÙØ§ Ø¨Ø§ÙØªØºØ±ÙØ¨. Ø¯ÙØª Ø§ÙØ¯Ø±Ø§Ø³Ø§Øª Ø§ÙØªÙ ÙØ§Ù Ø¨ÙØ§ Ø§ÙØ¹ÙÙØ§Ø¡ Ø¹ÙÙ Ø£Ù ÙÙÙÙØ© Ø§ÙØºØ±Ø¨ Ø¹ÙÙ Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØ³ÙÙ ØªÙÙÙ ÙÙ ÙÙØ§Ø¯ÙÙ ÙÙÙØ§ Ø§ÙØ¹ÙÙÙ ÙØ§ÙØ£ÙÙØ§Ø±. ÙØ£ØµØ¨ØØª ÙØ°Ù Ø§ÙÙÙÙÙØ© ØªØ¤Ø«ÙØ± ÙÙ Ø§ÙÙØ¸Ø±Ø© Ø§ÙØ¹Ø§ÙÙÙØ© ÙÙÙØ¬ØªÙØ¹ Ø§ÙÙØ³ÙÙ. ÙÙØ¹ Ø£Ù Ø§ÙÙØ¸Ø±Ø© Ø§ÙØ¹Ø§ÙÙÙØ© Ø£ØµØ¨ØØª Ø£Ø³Ø§Ø³Ø§ ÙÙÙÙ Ø§ÙÙØ§ÙØ¹ Ø§ÙÙØ¤Ø«ÙØ± ÙÙ Ø§ÙÙÙÙÙ ÙØ³ÙÙÙ Ø§ÙÙØ±Ø¯Ø Ø¨Ù Ø£ØµØ¨ØØª ÙØØ±ÙÙØ§ ÙÙØªØºÙÙØ± Ø§ÙØ§Ø¬ØªÙØ§Ø¹Ù. 2) Ø¯ÙØ± Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙ ØºØ±Ø³ Ø§ÙÙØ¸Ø±Ø© Ø§ÙØ¹Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙÙÙØ¬ØªÙØ¹ Ø§ÙÙØ³ÙÙ Ø¨Ø¯Ø§ÙØ© ÙÙ Ø§ÙÙÙÙ Ø£Ù ÙÙØ§Ù Ø¹ÙØ§ÙØ© ÙØ«ÙÙØ© Ø¨ÙÙ Ø§ÙØªØ±Ø¨ÙØ© ÙØ§ÙÙØ¸Ø±Ø© Ø§ÙØ¹Ø§ÙÙÙØ©. Ø£ØµØ¨ØØª Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© ÙØ³ÙÙØ© Ø£ÙÙÙØ© ÙÙ ØªÙÙÙÙ ÙÙØ¹ÙØ© Ø§ÙÙØ³ÙÙØ ÙÙØ°Ø§ ÙÙØ¨Ø¯Ø£ ÙÙ ØºØ±Ø³ ÙØªÙÙÙØ© Ø§ÙÙØ¸Ø±Ø© Ø§ÙØ¹Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ©. ÙÙØªÙÙÙØ© ÙØ°Ø§ Ø§ÙØ¯ÙØ±Ø ÙØªØ¬Ø¹Ù Ø§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙÙØ¸Ø±Ø© Ø§ÙØ¹Ø§ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø£Ø³Ø§Ø³Ø§ ÙØ¨ÙØ§Ø¡ Ø§ÙÙØ¸Ø§Ù Ø§ÙØªØ±Ø¨ÙÙ.